The impact of intravenous iodinated contrast agents on radiotherapy dose calculation and radiobiological effect predictions in central lung cancer - Yang, Defu; Shang, Feng; Xu, Ying; Yan, Ying (Frontiers in Oncology, 2025)
BackgroundAccurate dose calculation algorithms are critical for optimizing radiotherapy outcomes. This study evaluates and compares dosimetric differences and predictions of Tumor Control Probability (TCP) and Normal Tissue Complication Probability (NTCP) between the Analytic Anisotropic Algorithm (AAA) and Acuros XB (AXB) algorithm in lung cancer radiotherapy, under both contrast-enhanced and non-contrast enhanced CT conditions.MethodsTwenty patients with centralized lung cancer treated with intensity-modulated radiation therapy (IMRT) technique, including two patients with small cell lung cancer and 18 with non-small cell lung cancer, were selected to undergo CT scanning with and without contrast. Multiple dosimetric parameters were calculated for both algorithms under enhanced and non-contrast enhanced CT conditions. TCP and NTCP were assessed for critical organs such as the lungs, heart, and esophagus.ResultsSignificant differences were observed in dosimetric values between the AAA and AXB algorithms. For the minimum dose (PTV_Min), the AAA algorithm yielded higher values under enhanced CT conditions (4427 cGy) compared to non-contrast enhanced CT (3872 cGy), whereas AXB showed 4248 cGy (enhanced CT) and 3762 cGy (non-contrast enhanced CT). For maximum dose(PTV_Max), The AAA algorithm showed 6430 cGy (enhanced CT) compared to AXB's 6541 cGy (p< 0.0001). The mean dose (PTV_Mean) was 5674 cGy for AAA vs. 5640 cGy for AXB (p = 0.0042). TCP analysis showed that AAA predicted higher TCP values across both imaging conditions, with a 0.69% difference between AXB_C_Dm and AXB_C_Dw under enhanced CT (p = 0.0011). NTCP for lung radiofibrosis was 20.42% higher with the AAA algorithm, suggesting increased risk.ConclusionThe AAA algorithm tends to overestimate both tumor control and normal tissue complications, while the AXB algorithm provides more conservative estimates. These findings highlight the importance of algorithm choice in optimizing treatment planning and minimizing adverse effects in radiation therapy.